2014
DOI: 10.1186/1471-2261-14-165
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke increases cardiomyocyte ceramide accumulation and inhibits mitochondrial respiration

Abstract: BackgroundCigarette smoking is a common and lethal worldwide habit, with considerable mortality stemming from its deleterious effects on heart function. While current theories posit altered blood lipids and fibrinogen metabolism as likely mediators, none have explored the role of the sphingolipid ceramide in exacerbating heart function with smoke exposure. Ceramide production is a consequence of cigarette smoke in the lung, and considering ceramide’s harmful effects on mitochondrial function, we sought to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
(37 reference statements)
3
33
0
Order By: Relevance
“…As previously reported in CS-exposed mice fed regular chow [18], mice displayed reduced total body weight gain during CS exposure, even when fed HFD. This observation is consistent with known effects of CS to suppress appetite and increase energy expenditure [20]. Glucose and insulin tolerance largely followed weight patterns, and mice exposed to CS were more glucose tolerant and more insulin sensitive compared to HFD-fed non-exposed mice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As previously reported in CS-exposed mice fed regular chow [18], mice displayed reduced total body weight gain during CS exposure, even when fed HFD. This observation is consistent with known effects of CS to suppress appetite and increase energy expenditure [20]. Glucose and insulin tolerance largely followed weight patterns, and mice exposed to CS were more glucose tolerant and more insulin sensitive compared to HFD-fed non-exposed mice.…”
Section: Discussionsupporting
confidence: 88%
“…Exposure to CSE, derived from smoke condensate followed by removal of particulate matter, has been extensively used in ex vivo models [14][15][16][17][18]. Previous studies have reported a significant increase in ceramide in the lung and other tissues after experimental exposure to CS [18][19][20], so we also tested whether CS-exposure influenced β -cell ceramide content.…”
mentioning
confidence: 99%
“…Cells were prepared for mitochondrial respiration as described previously 27,28 before being transferred to respirometer chambers using the Oroboros O2K oxygraph. Electron flow through complex I was supported by glutamate + malate (10 mM and 2 mM, respectively) to determine leak oxygen consumption (GM L ).…”
Section: Mitochondrial Respirationmentioning
confidence: 99%
“…In particular, cigarette smoke pathologically alters sphingolipid metabolism, resulting in the accrual of ceramides, the backbone of higher-order sphingolipids, in heart [162] and skeletal muscle [178]—two key insulin-responsive tissues. Ceramide accrual in these tissues resulted in substantial disruption of mitochondrial function, including alterations in morphology and electron transport.…”
Section: Health Outcomes and Comorbiditiesmentioning
confidence: 99%
“…Research has even demonstrated that, after only 20 min of SHS exposure, direct endothelial cell injury is observed. Mechanistically, SHS exposure has been shown to increase free radicals [187] while decreasing antioxidants [188], decrease mitochondrial function [178], decrease protective HDL levels [189,190], and increase arterial stiffness [191]. Such staggering data adds new meaning to the current warnings from the Surgeon General that state “there is no safe level of exposure to tobacco smoke” [114].…”
Section: Health Outcomes and Comorbiditiesmentioning
confidence: 99%